Case Report: Dialysis following sintilimab-induced stage 3 acute kidney injury: mechanism investigation and management strategies - Shan, Bin; Li, Mengjiao; Yang, Ruixia; Wang, Guanqi; Hou, Juan; Wen, Tianjiao (Frontiers in Oncology, 2025)
Immune checkpoint inhibitors (ICIs) are widely used in the treatment of various tumor types. ICIs kill tumor cells by activating the body’s immune function. As this action is nonspecific, it inevitably triggers immune-related adverse events (irAEs), which can affect virtually all organs. Although the renal toxicity associated with ICIs such as pembrolizumab, nivolumab, and ipilimumab has been studied, research on domestically developed Chinese ICIs, including camrelizumab, sintilimab, tislelizumab, and toripalimab, remains limited. This paper presents the case of a lung cancer patient who developed stage 3 acute kidney injury (AKI) requiring dialysis following treatment with sintilimab. A literature review suggests that this is likely the second documented case of AKI necessitating dialysis after a single dose of sintilimab. Early recognition of irAEs, identification of risk factors, regular monitoring, steroid administration, and supportive care are crucial for improving patient outcomes. It should be emphasized that the tumor benefits of ICI therapy outweigh the risks of ICI-induced renal injury. In such cases, ICI treatment should not be discontinued or delayed, except in rare circumstances such as acute renal failure. When AKI occurs, healthcare professionals must be familiar with renal-related irAEs in order to facilitate the effective diagnosis and management of this increasingly common renal complication.